Extending IFC to incorporate information of RFID tags attached to building elements. Issue 1 (January 2016) - Motamedi, Ali; Soltani, Mohammad Mostafa; Setayeshgar, Shayan; Hammad, Amin
Highlights: We discussed the needs for adding definitions of RFID components to a BIM. We investigated scenarios to identify the related attributes of RFID system components. We investigated the relationships of RFID components with the assets/spaces. We proposed an IFC extension to incorporate the new definitions of RFID components. We validated and demonstrated the applicability of the proposed method through a real-world case study. Abstract: Building Information Modeling (BIM) is emerging as a method of creating, sharing, exchanging and managing the building information throughout the lifecycle between all stakeholders. Radio Frequency Identification (RFID), on the other hand, has emerged as an automatic data collection and information storage technology, and has been used in different applications in the AEC/FM (Architecture, Engineering, Construction, and Facilities Management) industry. RFID tags are attached to building assets throughout their lifecycle and used to store lifecycle and context aware information taken from a BIM. Consequently, there is a need for a standard and formal definition of RFID technology components in BIM. The goal of this paper is to add the definitions for RFID components to the BIM standard and to map the data to be stored in RFID memory to the associated entries in a BIM database. The paper defines new entities, data types, and properties to be added to the BIM. Furthermore, the paper identifies the relationships between RFID tags and building elements. These predefined relationships facilitate the linkage between BIM data and RFID data. Eventually, the data that are required to be saved on RFID tags can be automatically selected using the defined relationships in a BIM. A real-world case study has been implemented to validate the proposed method using available BIM software.